Hospital and oncological dental care: a series of cases - Thuanny Silva de MACÊDO; Maria Cecília Freire de MELO; Aurora Karla de Lacerda VIDAL (Faculdade São Leopoldo Mandic, 2019)
Hospital dental care is an educational and health care strategy whose purpose is to intervene, in a multidisciplinary way, in the health-disease process of vulnerable individuals, as unsatisfactory oral health is a risk factor for local and systemic infections. Patients in cancer treatment usually present oral manifestations because of the antineoplastic therapies to which they are submitted. Chemotherapy, radiation and cancer surgery, when the latter held in the head and neck region, have the potential to generate side effects in the oral cavity. These oral manifestations can be serious and interfere with the results of medical therapy, leading to important systemic complications, which can increase hospital stay, treatment costs, and affect the quality of life. In view of this reality, the incorporation of the dentist into the multiprofessional team in oncology is essential to guarantee the patient's integral care in all stages of therapy. This article then proposes to report a series of cases of patients attended at the Dentistry Service of the Oncology Center of the Oswaldo Cruz University Hospital of the University of Pernambuco, that exemplify the dental surgeon performance in a hospital environment, participating as an active member of a multidisciplinary team in oncology.